ANALISIS IMPLEMENTASI PROSEDUR PELAYANAN KOORDINASI MANFAAT DI RS ROEMANI MUHAMMADIYAH - Anggiyara Dayu Rizal; Putri Asmita Wigati; Anneke Suparwati (Jurnal Kesehatan Masyarakat (Undip), 2016)
Roemani Muhammadiyah Hospital is an advanced level referrasl health facility in Semarang that has been joined BPJS Kesehatan. The procedures of Coordination Of Benefit (COB) that implemented in Roemani Muhammadiyah Hospital were not optimal. It was because of some obstacles in communication, resource, disposition, and bureaucracy structure. This study was aimed to analyze the implementation of Coordination Of Benefit service procedures in Roemani Muhammadiyah Hospital. This study was a qualitative research that using indepth interview and observational method. Main informants are the policy implementor, those are head of insurance service sub-division, head of finance sub-division, finance division staff, and admission staff. The validity test used source triangulation to the head of Hospital’s JKN team and head of finance and accounting division. The findings of this study showed that the communication was not integrated, BPJS Kesehatan did not do socialization, less of written guidelines, and the policies were lack of consistance. The quality of human resource was not optimal. The staff disposition has been good by showing their each commitment. Bureaucracy structure was not good, because SOP of Coordination Of Benefit was not available, overlapping job, and the role of  Hospital’s JKN team was not optimal. The suggestions were internal policy and SOP making, build integrated communication system, training for the staffs, optimalizing role of Hospital’s JKN team.